Penerapan Perilaku Hidup Bersih dan Sehat Anak Usia Dini di Tengah Pandemi Covid-19 - Fandi Fandi; Andi Arniyanti; Erna Kasim; Nurbaiti Nurbaiti (Universitas Batanghari Jambi, 2022)
Covid-19 is a new type of disease thought to have originated from infection with the acute respiratory syndrome coronavirus 2 (SARSCOV 2). In preventing the transmission of covid-19 in children through a clean and healthy lifestyle for all children. this study aims to determine how to apply clean and healthy living behavior in early childhood in the midst of the covid-19 outbreak. this study uses quantitative evidence using the Garuda and Google Scholar databases. As a result, there are 4 articles that became the main reference in the preparation of this research. the authors can see that there is a significant effect on the implementation of clean and healthy living behavior in early childhood in the mist of the covid-19. Based on research results from effective books and literature that the application of clean and healthy living behavior in early chilhood is very effective. This can be seen from parents and children who are obedient in carrying out various kinds of self-accustoming to clean and healthy behavior in the midst of the covid-19.